Incidence and Management of Hairy Caterpillar (Spilarctia obliqua Walker) on Sesame - Biswas, GC (Journal of Agriculture & Rural Development, 2008)
Incidence and management of hairy caterpillar, Spilarctia oblique (Walk.) on sesame were studied in the field and laboratory of the Oilseed Research Centre, BARI, Gazipur, during March to July, 2000 and 2001, respectively. The pest appeared in the sesame crop in the fourth week of April at the flowering stage at 45-55 Days After Sowing (DAS) and remained up to third week of June at the pod maturity stage at 90-95 DAS. The peak populations of S. oblique (4.00 4.50 larvae per plant) and their severe infestation (100% plant) were recorded in the fourth week of May, at the pod filling stage at 60-70 DAS of the crop. The yield reduction of sesame caused by S. obliqua in the treatments 1 spray, 2 sprays, 3 sprays, and 4 spray frequencies with Diazinon 60 EC @ 2 ml/litre were calculated 25.00, 30.86, 35.24 and 37.23 percent, respectively. One spray of Diazinon 60 EC applied at the pod formation stage at 50-55 DAS gave the highest benefit cost ratio (4.20). Key words: Incidence, hairy caterpillar, sesame, infestation, management.